Abuse of Drugs "for Kicks": A Review of 252 Admissions. Issue 5885 (20th October 1973) - Forrest, John A. H.; Tarala, Richard A.
Abstract : Abuse of drugs "for kicks" is becoming more common in Great Britain. This article reviews 252 consecutive cases of drug abuse admitted to the Regional Poisoning Treatment Centre, Royal Infirmary, Edinburgh, during 1971 and 1972. Of the 189 patients (146 males and 43 females; mean age 20 years) 72% of admissions occurred between 6 p.m. and 8 a.m., and Saturday was the most common day for admissions. The commonest source of referral was via the police or ambulance service. Barbiturates were the drugs most often abused, followed by LSD (lysergide) and Mandrax (methaqualone and diphenhydramine). Sixty-five per cent. of patients had previously abused drugs. Medical care was required in 45% of the admissions. Sixty per cent. were in social class 4 or 5 and psychiatric and social support was required in only a small minority of patients.